The severity of anaemia depletes cerebrovascular dilatory reserve in children with sickle cell disease: a quantitative magnetic resonance imaging study. (1st December 2016) - Kosinski, Przemyslaw D.; Croal, Paula L.; Leung, Jackie; Williams, Suzan; Odame, Isaac; Hare, Gregory M. T.; Shroff, Manohar; Kassner, Andrea
Summary: Overt ischaemic stroke is one of the most devastating complications in children with sickle cell disease (SCD). The compensatory response to anaemia in SCD includes an increase in cerebral blood flow (CBF) by accessing cerebrovascular dilatory reserve. Exhaustion of dilatory reserve secondary to anaemic stress may lead to cerebral ischaemia. The purpose of this study was to investigate CBF and cerebrovascular reactivity (CVR) using magnetic resonance imaging (MRI) in children with SCD and to correlate these with haematological markers of anaemia. Baseline CBF was measured using arterial spin labelling. Blood‐oxygen level‐dependent MRI in response to a CO2 stimulus was used to acquire CVR. In total, 28 children with SCD (23 not on any disease‐modifying treatment, 5 on chronic transfusion) and 22 healthy controls were imaged using MRI. Transfusion patients were imaged at two time points to assess the effect of changes in haematocrit after a transfusion cycle. In children with SCD, CBF was significantly elevated compared to healthy controls, while CVR was significantly reduced. Both measures were significantly correlated with haematocrit. For transfusion patients, CBF decreased and CVR increased following a transfusion cycle. Lastly, a significant correlation was observed between CBF and CVR in both children with SCD and healthy controls.